ANALISIS PRODUKTIVITAS BATCHING PLANT READYMIX CONCRETE TIPE WETMIX DENGAN METODE TIME STUDY - Fahmi Al Farabby Mustofa; Anna Rumintang Nauli; Elok Dewi Widowati (LPPM Universitas Abdurrab, 2026)
The selection of heavy equipment has a significant impact on the efficiency and effectiveness of a project. In this study, a batching plant was chosen because readymix concrete is a sensitive component in the construction sector that can be optimized to save time and costs.This research aims to identify the stages of concrete production at a wetmix batching plant, determine the level of productivity achieved, compare the results with the company's standard productivity benchmarks, and analyze the factors influencing production activities during the observation period. The study employed direct measurement methods by observing the operator's tasks and recording the time taken. The research approach used is based on the time study method. The focus of the study is on the productivity of a wetmix type batching plant in producing Fc’ 30 grade concrete with the addition of fly ash. An analysis was then conducted to determine the cycle time, production capacity, and a comparison of productivity against the company’s standard benchmarks. The productivity of the wetmix batching plant in producing readymix concrete on May 5 and 6, 2025, averaged 84.76 m³/hour per cycle. Therefore, the batching plant of Company X has not yet met the company’s standard productivity requirements.